EFFECT OF CHAMBER PRESSURE ON ELECTRICAL IMPEDANCE OF A LOW-FREQUENCY NITROGEN PLASMA IN A MEDIUM VACUUM REACTOR - Dionysius Joseph Djoko Herry Santjojo (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Brawijaya, 2017)
The character of a low-frequency nitrogen plasma in a medium vacuum reactor was studied by determining the effect of chamber pressure on the electrical impedance of the plasma. The system understudied was a mini capacitive plasma reactor utilizing 40 kHz generator. The pressure was varied from 0.4 – 4.7 torrs. Results of this work indicated that the pressure in the range significantly affects the electrical impedance. The increase of the chamber pressure decreased the capacitive reactance while increased the resistance. The capacitive plasma indicates the plasma was controlled by excitation and ionization process, while the resistive plasma exhibits complex reactions due to collisions.